Guidelines for the Development of Occupational Standards of Community Based Tourism Enterprise Group of Taling Chan Community, Taling Chan Sub-district, Ban Dan Lan Hoi District Sukhothai - Phasuwan, Boonchan; Pruekaporn, Suvita (Journal of Public Administration Chiang Rai Rajabhat University, 2022)
Establish guidelines for the development of occupational standards for community-based tourism enterprises with participation of Taling Chan Community, Taling Chan Subdistrict, Ban Dan Lan Hoi District Sukhothai province due to Joint planning of the section It will be the driving force of working in the broader and will not be redundant. Tourism operators propose the development of products and services by mainly studying tourists’ behavior, safety and sanitation standard issues, as well as having a positive attitude towards the model of community-based tourism activities. Therefore, those involved in community-based tourism management should also have a tourism plan. Caution can reflect the concept in a positive light Safe, standardized, avoiding a precarious image that leads to disgrace.